O naturalismo ético no behaviorismo radical de B. F. Skinner - Castro, Marina Souto Lopes Bezerra de (Universidade Federal de São Carlos, 2013)
We presuppose the existence of an Ethics in Skinner's work. It reveals, at least, three aspects: a Metaethics, a Normative and an Applied Ethics, which will be detailed in the present investigation. Before this, we will try to present chronologically the development of his ideas related to this topic. We conclude that the Skinnerian Ethics may be considered as a Naturalistic one. We attempt to describe it. Inside the Naturalistic Ethics, Skinner proposes something interesting, relevant, well founded, both in relation to a methaethics as well as in relation to the principles for an applied ethics. There are questionable points, one of them indicated in our last work, that is the attempt to traduce/reduce prescriptive aspects into descriptive ones, disregarding the difference between the causal determinants for tacts and those for mands. In this approach, we will essay a depth analysis, identifying what maybe is the core, or final, aspect of this tension: the defense of a technocracy, a huge problem found in the Skinnerian Ethics. What would be the limit for the technical authority? Prescriptions based on scientific knowledge are fully appropriate and acceptable, but what would be the limit for the derivation of mands from scientific evidence? Is there an alternative? Our thesis is this: Skinnerian Ethics is a kind of Naturalistic Ethics, and its main limitation is the defense of a technocracy.
Keywords: Behaviorismo (Psicologia); Ética; Skinner, B. F. (Burrhus Frederick), 1904-1990; Behaviorismo radical; Falácia naturalista; Behaviorismoradical skinneriano; Tecnocracia; Ethics; Naturalistic fallacy; Skinner's radical behaviorism; Technocracy; CIENCIAS HUMANAS::FILOSOFIA